What Althusser Can Teach Us about Street Theater – and Vice Versa - Moder, Gregor (Stasis, 2014)
The defining trait of street performances is that they catch their audience members unawares, while they are walking on the streets minding their own business. They recruit unsuspecting pedestrians and transform them into active participants in a street performance. This is what enables us to compare the transformative operation of street theater to what philosopher Louis Althusser described as the operation of ideological interpellation. In the first part of the paper the author discusses several ways of separating these two interpellations, drawing from examples by Robert Pfaller, Mladen Dolar, Slavoj Žižek and Blaise Pascal. In the second part of the paper, the author discusses examples of the Slovenian group Laibach, interventions by the Rebel Clown Army and the “Standing Man” protests in Turkey, arguing that artistic practices can be subversive with respect to the dominant ideology, when they are able to occupy the position of ideology’s blind spot.